Determinants of Community Welfare in Southeast Sulawesi, Indonesia - Hasddin; Jacob Breemer; Abd. Azis Muthalib; La Ode Suriadi; Lapipi; La Karimuna; Melati; Rola Pola Anto; Misnawati; Nartin; Asri Nova Rama (Research Synergy Foundation, 2025)
Community welfare is a fundamental objective in achieving sustainable and equitable development, particularly in regions facing persistent urban–rural disparities. Despite various policy interventions, including fiscal transfers and targeted development programs at local levels, the determinants of community welfare remain a subject of debate. This study examines the key economic determinants of community welfare in Southeast Sulawesi Province, Indonesia, focusing on economic growth, income inequality, labor absorption, infrastructure availability, and investment. Using panel data regression analysis, this study investigates the causal relationships between these economic factors and community welfare across districts and cities in Southeast Sulawesi from 2012 to 2021, based on data from the Central Statistics Agency. The results indicate that labor absorption, income inequality, infrastructure development, and investment have significant effects on community welfare. Employment emerges as the most influential factor, suggesting that higher labor absorption plays a critical role in improving welfare outcomes. Income inequality shows a significant negative effect, indicating that increasing disparities reduce overall welfare. Infrastructure development and investment positively contribute to welfare by enhancing public services and expanding employment opportunities. In contrast, economic growth demonstrates a weaker impact compared to other determinants. This study contributes to the literature by providing empirical evidence that community welfare is more strongly influenced by employment creation and inequality reduction than by economic growth alone. The findings offer important policy implications for regional development planning, emphasizing the need for inclusive, labor-oriented, and infrastructure-supported development strategies to enhance welfare in developing regions.